ANALISIS PENEMPATAN DAN MOTIVASI DALAM HUBUNGAN KINERJA KARYAWAN PADA PT. BANK PAPUA KANTOR CABANG KOTA MANADO - Justince M. E. Abidondifu; Dolina L. Tampi; Tinneke M. Tumbel (Universitas Sam Ratulangi, 2017)
The absolute necessity of a strong human resource can not bedenied in facingthis new era. Organization or company will meet a form of competition that is more complexwith variation, intensity and coverage that may not been experienced before. Therefore, organization needs strong people, who can be able to adapt any changes that occur, and able to work in new ways through their skills and duties. Sedermayati (2011:120)said that, placement means assignment of returning employees to new jobs or positions. According to sulistiyani (2011:193) motivation is part of MSDM, in the framework of coaching, development and direction of manpower within an organization. The method that is used in this research is descriptive quantitative with research that searches for the exact facts and interpretation to gain result that can be achieved using the statistics procedure or other ways of quantification (measurement). The results of this study show that replacement and motivation has a very high effect on employee performance, therefore effective performances should be more optimized.The results of this study show that placement and motivation affect the performance employees so that the effectiveness of performance becomes more optimal. The influence of placement and motivation in the relationship of employee performance has a positive impact, because the company is very good attention to the needs of employees. Employee work experience and employee morale become a benchmark for the implementation of good performance. Â Keywords: Analysis Placement and Motivation, Employee Performance.